Analysis of Existential Presumptions in Raffi Ahmad and Nagita Slavina's Vlog in the Rans Entertainment Youtube Channel - Adistia Azara Ramadhani; Eva Eri Dia (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
Research with the title pragmatic study: Analysis of Existential Presuppositions on Raffi Ahmad and Nagita Slavina's Vlogs on the RANS Entertainment YouTube Channel. The aims of this study are: (1) to find out the existential presuppositions contained in vlogs, (2) to identify existential presuppositions contained in vlogs, and (3) to analyze existential presuppositions contained in Raffi Ahmad and Nagita Slavina's vlogs on the RANS Entertainment YouTube channel with using (George Yule's theory in Dia, 2012). The method used in this research is descriptive qualitative method. The source of the data in this study is speech contained in vlogs on the RANS Entertainment YouTube channel, while the research data is in the form of grammatical units in the form of words, phrases or sentences that contain existential presuppositions. This research instrument uses a documentation study. Data collection techniques in this study used documentation analysis techniques, while data analysis used in this study was descriptive analysis techniques. The results of this study analyze the existential presuppositions contained in Raffi Ahmad and Nagita Slavina's vlogs on RANS Entertainment's YouTube channel.